1999
DOI: 10.1002/(sici)1096-9861(19990531)408:2<272::aid-cne8>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual system of the european hummingbird hawkmoth Macroglossum stellatarum (sphingidae, lepidoptera): Motion-sensitive interneurons of the lobula plate

Abstract: The European hummingbird hawkmoth Macroglossum stellatarum is a member of the sphingid family, denoted by their ability to hover in place in front of flowers. The fast and acrobatic flight behavior is thought to be under the control of the optomotor system both during normal, forward flight and during stationary, hovering flight. Electrophysiologic and neuroanatomic studies presented here reveal large-field, motion-sensitive neurons in the lobula plate. Anatomic and physiologic features characterize these nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A pair of directionally‐selective neurons with opposite preferred directions against each other has been identified in several insects such as flies (e.g., Gilbert & Strausfeld, ; Hausen, ), honeybees (Ibbotson, ), hawkmoths (Wicklein & Varju, ), and locusts (Rind, ). In flies, some of directionally selective neurons project to ipsilateral protocerebrum and the others to contralateral protocerebrum, and the enhancement of responsiveness by excitatory input from the contralateral neuron has been reported (Hausen, ).…”
Section: Discussionmentioning
confidence: 99%
“…A pair of directionally‐selective neurons with opposite preferred directions against each other has been identified in several insects such as flies (e.g., Gilbert & Strausfeld, ; Hausen, ), honeybees (Ibbotson, ), hawkmoths (Wicklein & Varju, ), and locusts (Rind, ). In flies, some of directionally selective neurons project to ipsilateral protocerebrum and the others to contralateral protocerebrum, and the enhancement of responsiveness by excitatory input from the contralateral neuron has been reported (Hausen, ).…”
Section: Discussionmentioning
confidence: 99%
“…They respond to a preferred vertical as well as to a preferred horizontal direction, suggesting that their dendrites receive inputs from two converging popu-lations of lobula plate outputs: horizontal motion-sensitive neurons and vertical motion-sensitive neurons. Recent studies of the diurnal hummingbird hawk moth Macroglossum stellatarum (Wicklein and Varju, 1999) have confirmed that the sphingid lobula plate indeed provides separate populations of vertical and horizontal motionsensitive tangential neurons that are probably homologous to the horizontal and vertical motion-sensitive neurons of many brachyceran Diptera (Buschbeck and Strausfeld, 1997).…”
Section: Polarities Of Looming Neuronsmentioning
confidence: 96%
“…In moths, as in flies, optic cartridges consist of columnar arrays of parallel axonal fibers synapsing multitudes of times with neurons residing in four integrative layers of visual neuropil in the optic lobe: the lamina, medulla, lobula, and lobula plate. Research on moths' visual motion resolution within these layers (Collett and Blest 1966;Collett 1970Collett , 1972Strausfeld and Blest 1970;Ibbotson et al 1991;Maddess et al 1991;Tominaga 1991, 1999;Milde 1993;Cutler et al 1995;Hämmerle and Kolb 1997;Wicklein and Varju 1999;Wicklein and Strausfeld 2000;Briscoe et al 2003;Kelber et al 2003;Stavenga and Arikawa 2006) shows that image-motion integration through these levels does not appear to differ in significant ways from that of flies, upon which most of the classic work in image-motion integrative pathways has been performed (Strausfeld and Campos-Ortega 1977;Douglass and Strausfeld 1996, 2003. As in flies, six receptor neurons (R1-R6) of the eight in each ommatidia of moths and butterflies are tuned to the same single wavelength optimum, similar to the six R1-R6 receptor neurons in fly ommatidia that synapse into several flicker-sensitive optic cartridge channels of the large monopolar cells (LMCs) in the lamina (figure 10.2B).…”
Section: The Lepidopteran Visual Systemmentioning
confidence: 99%
“…the parallel and tightly packed arrangement of Kenyon cells, their vast numbers and arborizations with sensory projection neurons in the calyx, and their synaptic multimodal inputs and outputs with protocerebral neurons along their entire lengths in the mushroom body lobes all facilitate information processing and dispensation in the mushroom body that is essential to the life and reproduction of an insect (from Sjöholm et al 2005). ized (Wicklein and Varju 1999). Such lobula plate neurons, called "vertically sensitive" (VS) and "horizontally sensitive" (hS), are a common feature of many dipteran and lepidopteran lobula plates.…”
Section: The Lepidopteran Visual Systemmentioning
confidence: 99%